Violation of women family functioning after suffering a psychotic episode - Aymedov, Сonstantin; Baskinа, Viktoriia (Psychiatry, Neurology and Medical Psychology, 1970)
Modern authors considered that manifest mental illness affects all aspects of family life and is a heavy psycho-emotional stress associated with the onset of disease, loss of shortterm and long-term plans for the future challenges of patient care, financial stress, a decrease in social activity. In the present article, the authors present the results of the research whose purpose was to detect disturbances in the functioning of a family of women who have had a primary psychotic episode. Between 2010 and 2016, we examined 219 women who underwent first psychotic episode, and their husbands. The first group included 101 women who have no children, and the second group consisted of 118 women who have a child. The studying included an assessment of the quality of life of patients, diagnosis of family relationships, the level of satisfaction withmarriage and definitions related to the parental role. The studying showed that women who have had a primary psychotic episode, have got general decline in the quality of life, dissatisfaction with their relationship in marriage, role in family life and its lack of independence. Women with children have got violations of emotional contact with the child.